DAMPAK POLIGAMI TERHADAP KEHARMONISAN KELUARGA DI LUBUK BARUMUN - Maharani Erni (Yayasan Baitul Hikmah al-Zain, 2024)
Polygamy, where a man marries more than one woman, can significantly impact family dynamics. This study aims to analyze the effects of polygamy on family structure, emotional well-being, and relationships among family members. A qualitative approach was used, involving in-depth interviews with 10 polygamous families in urban areas. The collected data were analyzed using thematic analysis to identify recurring patterns and issues. The findings suggest that polygamy can lead to tensions between wives and children, affect communication quality, and create imbalances in the distribution of attention and resources. However, some families reported that polygamy helped strengthen relationships between wives and improved the family’s economic well-being. In conclusion, the impact of polygamy on families is varied and influenced by factors such as communication, power balance, and the family’s values. Therefore, a more nuanced approach is needed to understand and manage polygamy in different social and cultural contexts.